Faces in the forest : First Nations art created on living trees - Blackstock, Michael D., 1961- (McGill-Queen's University Press, 2001)
In Faces in the Forest Michael Blackstock, a forester and an artist, takes us into the sacred forest, revealing the mysteries of carvings, paintings, and writings done on living trees by First Nations people. Blackstock details this rare art form through oral histories related by the Elders, blending spiritual and academic perspectives on Native art, cultural geography, and traditional ecological knowledge. Faces in the Forest begins with a review of First Nations cosmology and the historical references to tree art. Blackstock then takes us on a metaphorical journey along the remnants of trading and trapping trails to tree art sites in the Gitxsan, Nisga'a, Tlingit, Carrier, and Dene traditional territories, before concluding with reflections on the function and meaning of tree art, its role within First Nations cosmology, and the need for greater respect for all of our natural resources. This fascinating study of a haunting and little-known cultural phenomenon helps us to see our forests with new eyes.